1961
DOI: 10.1002/asi.5090120104
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of new scientific information: A preliminary report

Abstract: TO INVESTIGATE the metabolism of new scientific information, questionnaires were sent to the authors of 463 papers presented or "read by title" at two important meetings for cardiovascular and endocrine research workers. The preliminary findings indicate that, of the approximately 60% of authors responding, about one-third submitted their papers for publication before, or within 6 months after, the meeting. The interval between submission and publication was around 6 months. Less than 60% of the papers on whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…We excluded 14: three were not about biomedical meetings [5-7], six were on collections of abstracts across meetings that were not identifiable individually [8-13]; and in five, relevant data could not be extracted [14-18]. We analysed data from 64 studies published in 70 reports [1,3,19-86] (see Additional file 1). Four of those studies were published in two full reports each and with partial overlap of the data [1,45,46,50,51,62,74,84].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We excluded 14: three were not about biomedical meetings [5-7], six were on collections of abstracts across meetings that were not identifiable individually [8-13]; and in five, relevant data could not be extracted [14-18]. We analysed data from 64 studies published in 70 reports [1,3,19-86] (see Additional file 1). Four of those studies were published in two full reports each and with partial overlap of the data [1,45,46,50,51,62,74,84].…”
Section: Resultsmentioning
confidence: 99%
“…We analysed data from 64 studies published in 70 reports [1,3,19-86] (see Additional file 1). Four of those studies were published in two full reports each and with partial overlap of the data [1,45,46,50,51,62,74,84]. Another study was published in three abstracts with substantial redundancy of the reported data [79-81].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first asked students, “Did you deliver any papers at national scholarly meetings?” Presenting at national meetings is an important precursor to publication and signals active engagement in the research enterprise [15]. A second question in this survey asked, "Were you encouraged by faculty in your department to publish?"…”
Section: Methodsmentioning
confidence: 99%